Synthesis and Biological Activity of Sulphadiazine Schiff´ s Bases of Isatin and their N-Mannich Bases - SINGH, B.N.; SHUKLA, S.K.; SINGH, MEERA (Asian Journal of Chemistry, 2010)
Sulphadiazinyl Schiff bases of isatin (and derivatives) and their Mannich bases were synthesized. Their chemical structures have been confirmed by IR, 1H NMR and by elemental analysis. Antimicrobial evaluation were done against pathogenic bacteria and fungi. Nearly all the synthesized compounds exhibited antimicrobial activity against gram positive and gram negative bacteria at 500 μg concentration.